JEFRI CHOSER – INGLIZ SHE’RIYATINING ATOQLI NAMOYONDASI (Journal of Universal Science Research, 2025)
This thesis explores the works of Geoffrey Chaucer, regarded as one of the greatest figures in English literature, with a particular focus on his masterpiece “The Canterbury Tales”, as well as other notable examples of his creative legacy. Although the work is considered unfinished, it has captured the hearts of English-speaking readers for centuries. The thesis not only provides comprehensive information about the work and its author but also offers a close examination of Chaucer as a beloved literary figure, comparable to Alisher Navoi for the Uzbek people.